Significance of radiology in the diagnosis and management of ruptured left gastric artery aneurysm associated with acute pancreatitis: Case report. Issue 10 (March 2019) - Valluru, Bimbadhar; Yang, Bin; Sharma, Kalyan; Adam, Ahmed Abdullahi; Wei, Du; Zhou, Zhou; Ali, Mahamed Osman
Abstract: Rationale: Left gastric artery aneurysms are very rare which progresses into hemorrhagic shock and diagnosis is very challenging particularly in patients with acute pancreatitis and cholecystitis whose vitals become unstable suddenly. Patient concerns: A 72-year-old female has presented with severe progressing abdominal pain was treated with total parenteral nutrition for acute pancreatitis based on preliminary work up, but suddenly became unstable with dropping vitals over the ensuing 48 hours. Physical examination has a positive Murphy sign and appeared lethargic. She has no past history of any chronic systemic illness or malignancy. Diagnoses: Ruptured left gastric artery aneurysm and left hepatic artery aneurysm with intraperitoneal hemorrhage associated with acute pancreatitis and cholecystitis. Interventions: Emergency interventional surgery was performed to embolize both the aneurysms and the giant aneurysmal sac of the left gastric artery was secured with a micrometallic occluding coil which eventually controlled the active hemorrhage. Outcomes: The patient became stable and was discharged after 15 days without any recurrence or complications during the 6-month follow-up. Lessons: This case is a peculiar example of a missed diagnosis of left gastric artery aneurysm associated with acute pancreatitis and cholecystitis with deteriorating clinical condition. Exhaustive radiological investigations are necessary for early diagnosis correlating with presenting clinical situations. Radiologists should be familiar with the challenges in diagnosis and management.